EFFICACITÉ D’UTILISATION DE LA TECHNIQUE DU VIRELANGUE POUR AMÉLIORER LA COMPÉTENCE DE LA PRONONCIATION DES VOYELLES NASALES - Aprianti Monthia Manik; Fibriasari Hesti (Franconesia, 2026)
This study aims to measure the effectiveness of the virelangue (tongue twister) technique in improving the pronunciation ability of French nasal vowels ([œ̃], [ã], [ɛ̃], [ɔ̃]) among grade XII students of SMAN 1 Lubuk Pakam. The research method employed was a quasi-experimental approach with a One Group Pretest-Posttest design. The sample consisted of 30 students from class XII I, selected through initial observation. Data collection was carried out using oral production tests (voice recordings) administered before (pre-test) and after (post-test) three sessions of pedagogical treatment. Data were analyzed using the non-parametric Wilcoxon Signed Rank Test via SPSS because the data distribution was non-normal according to the Shapiro-Wilk test (p < 0.001). The descriptive statistics revealed a significant increase in the students' mean score, rising from 40.00 in the pre-test to 66.67 in the post-test. Based on the Wilcoxon test, the Asymp. Sig. (2-tailed) value was < 0.001 (p < 0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). In conclusion, the virelangue technique is significantly effective in enhancing French nasal vowel pronunciation skills and boosting students' confidence at SMAN 1 Lubuk Pakam.